Pengaruh Penerapan Total Quality Management Terhadap Kepuasan Jamaah Umrah Pada PT. Mustika Kartika Samudera - Fellasufah Diniyah; Amirudin Amirudin (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2019)
The purpose of this study is to study the importance of applying the Total Quality Management Application to the satisfaction of Umrah pilgrims at PT. MustikaKartikaSamudera. The research method used in this research is quantitative, with the sample used in this study were 92 respondents by using purposive sampling method. The results of the study indicate a link between the application of TQM and satisfaction of moderate worshipers. Then, the application of a significant effect on the application of Total Quality Managementis alsorelated to the satisfaction of Umrah pilgrims. The coefficient value is determined at 45.9%.This figure shows that 45.9% satisfaction of pilgrims that occur is influenced by Total Quality Management, and the remaining 54.1% is influenced by other factors.